2017
DOI: 10.1111/bcp.13324
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetic interaction between ivacaftor and ritonavir in healthy volunteers

Abstract: Ritonavir resulted in significant inhibition of the metabolism of ivacaftor. These data suggest that ritonavir may be used to inhibit the metabolism of ivacaftor in patients with cystic fibrosis (CF). Such an approach may increase the effectiveness of ivacaftor in 'poor responders' by maintaining higher plasma concentrations. It also has the potential to significantly reduce the cost of ivacaftor therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…For verification simulations, the dose and schedule of drugs were matched to the design of the corresponding clinical DDI studies in healthy participants. 11 , 12 , 13 , 21 To quantify the DDIs, the geometric mean ratios of AUC or C max with or without the presence of CYP3A4 modulators were calculated. The assessment of DDI prediction success was based on whether predictions were within a twofold range of the observed data.…”
Section: Methodsmentioning
confidence: 99%
“…For verification simulations, the dose and schedule of drugs were matched to the design of the corresponding clinical DDI studies in healthy participants. 11 , 12 , 13 , 21 To quantify the DDIs, the geometric mean ratios of AUC or C max with or without the presence of CYP3A4 modulators were calculated. The assessment of DDI prediction success was based on whether predictions were within a twofold range of the observed data.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we examined the P-gp structure in the presence of ivacaftor. In order to minimize non-specific binding of the hydrophobic drug, we employed a concentration likely to be encountered in vivo [28] and at a sub-stoichiometric ratio with the protein. This approach had the advantage of allowing both drug-bound and drug-free forms of the protein to coexist as a mixture in the protein/drug solution immediately prior to flash freezing and cryo-electron microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we aimed to provide guidance for ETI dose adjustment with ritonavir, the CYP3A inhibitor and the component of nirmatrelvir/ritonavir for the treatment of COVID-19. From the ETI-ritonavir DDI simulations, we found that when ritonavir 100mg q12h was administered for 5 days, it led to the AUC ratio of ivacaftor as 9.31 (90% CI: 8.28, 10.47) which far exceeded the observed and simulated AUC ratio (3.06) when ivacaftor was administered with ritonavir 50 mg q24h(22). The increase in interaction with the therapeutic regimen shows that dose adjustments should not be estimated purely on the basis of the available clinical study.…”
Section: Discussionmentioning
confidence: 94%
“…For tezacaftor, the itraconazole solution (200 mg) was administered BID on Day 1 and QD from Day 2 to Day 14 and tezacaftor 25 mg was administered daily from Day 1 to Day 14 (12). For ivacaftor, four clinical DDI studies were conducted with ritonavir, ketoconazole, fluconazole, or rifampin (11,22). For ritonavir, 50mg was administered daily from Day 1 to Day 18 and a single 150 mg dose of ivacaftor was administered on Day 15.…”
Section: Model Verification: Ddi Simulationsmentioning
confidence: 99%